AIDS, Access to Medicines, and the Different Roles of the Brazilian and South African Governments in Global Health Governance - Jan Peter Wogart; Gilberto Calcagnotto; Wolfgang Hein; Christian von Soest (German Institute of Global and Area Studies (GIGA), 2008)
The present article illustrates how the main actors in global health governance (GHG) - governments, nongovernmental organizations (NGOs), intergovernmental organizations (IOs), and transnational pharmaceutical companies (TNPCs) - have been interacting and, as a result, modifying the global health architecture in general and AIDS treatment in particular. Using the concept of 'power types' (Keohane/Martin) and 'interfaces' (Norman Long), the authors examine the conflicts among major GHG actors that have arisen surrounding the limited access to medicines for fighting HIV/AIDS basically as a result of the Agreement on Trade Related Intellectual Property Rights (TRIPS), in force since 1995. They then analyze the efforts of Brazil and South Africa to obtain fast and low-cost access to antiretroviral medication against AIDS. They conclude that while policy makers in the two countries have used different approaches to tackle the AIDS problem, they have been able, with the support of NGOs, to modify TRIPS and change some WTO rules at the global level along legal interfaces. At the national level the results of the fight against AIDS have been encouraging for Brazil, but not for South Africa, where authorities denied the challenge for a prolonged period of time. The authors see the different outcomes as a consequence of Brazil's ability to combine discoursive, legal, administrative, and resource-based interfaces. – – Dieser Aufsatz zeigt, wie die Hauptakteure von global health governance - Regierungen, Nichtregierungsorganisationen (NGOs), intergouvernementale Organisationen (IOs) und die transnationalen pharmazeutischen Unternehmen (TNPCs) - durch intensive Interaktionen die globalen Regelungen zum Gesundheitswesen im Allgemeinen und zur Behandlung von AIDS im Besonderen entscheidend modifiziert haben. Ausgehend vom Begriff der verschiedenen Machtformen (Keohane/Martin) und Schnittstellen (interfaces, Norman Long), untersuchen die Autoren die Konflikte zwischen den genannten Akteuren, entstanden aus dem beschränkten Zugang zu den teuren antiretroviralen HIV/AIDS-Medikamenten - u.a. eine Folge des 1995 in Kraft getretenen Agreement on Trade Related Intellectual Property Rights (TRIPs). Sie gehen sodann auf die unterschiedlichen Politiken der AIDS-Bekämpfung in Brasilien und Südafrika ein und kommen zu dem Schluss, dass diese Länder es zwar gemeinsam mit anderen Ländern und den NGOs geschafft haben, einige WTO-Regeln auf globaler Ebene zu verändern, dass die Ergebnisse auf nationaler Ebene jedoch auseinanderklaffen - enttäuschend für Südafrika, wo das Problem lange Zeit ignoriert wurde, und ermutigend für Brasilien, dank einer gelungenen Kombination der diskursiven, legalen, organisatorischen und ressourcenbezogenen interfaces.
Keywords: 300; global health governance; HIV/AIDS in Brazil and South Africa; discoursive; legal; organizational and resource-based interfaces; WTO; transnational pharmaceutical companies; NGOs